KINERJA ALGORITMA PARALEL UNTUK PENCARIAN KATA DENGAN METODE BOYER-MOORE MENGGUNAKAN PVM - Maria Angela Kartawidjaja; Stania Vandika (JUTI: Jurnal Ilmiah Teknologi Informasi, 2009)
Search process is one of important activity in data processing. Searching can take more time if conducted in the huge search space. Therefore, it is needed an efficient search technique. One technique that can be used is parallel computing. This article discusses the search process in parallel using the Boyer-Moore algorithm. Parallel scope is emulated with PVM (Parallel Virtual Machine) software. From the research results, it can be concluded that the performance of parallel computing will increase the word searching compared to the computing performance for its word sequencial search consisting of one letter, and will drop to the word search consisting of two letters or more.